Analysis of geometric imperfections of spirally welded slender steel tubes. (January 2020) - Mirzaie, Fariborz; Myers, Andrew T.; Jay, Angelina; Mahmoud, Abdullah; Smith, Eric; Schafer, Benjamin W.
Abstract: The objective of this paper is to analyze and characterize high-resolution measurements of geometric imperfections taken from a set of seven slender tapered steel tubes in order to provide insights that can improve methods for predicting buckling behavior. The seven tubes are each ~3400 mm long with diameters between 800 mm and 1100 mm, diameter to thickness ratios between 300 and 350, and taper angles between 0.67° and 0.86°. The tubes are manufactured from steel plates using an innovative spiral welding process. The geometric imperfections of these tubes are characterized with harmonic analysis of the overall imperfection measurements and with regression analysis of the measured shapes of weld depressions. The results show a consistent imperfection signature caused by the manufacturing process including distinct features attributed to both the rolling and welding processes, i.e. anticlastic deformations and weld depressions. Variability in the imperfection measurements is also analyzed and used to generate a probabilistic scheme capable of generating random fields of geometric imperfections that are consistent with the measurements considered here. Highlights: High-resolution imperfection measurements of seven slender tubes are analyzed. Characteristic geometric imperfections in spirally welded tubes are identified. Distributions of the magnitude of spiral weld-induced depressions are characterized. A probabilistic model to generate random imperfections in slender tubes is proposed.